2011
DOI: 10.1155/2011/761593
|View full text |Cite
|
Sign up to set email alerts
|

Collagen‐Based Films Containing Liposome‐Loaded Usnic Acid as Dressing for Dermal Burn Healing

Abstract: The aim of this study was assess the effect of collagen-based films containing usnic acid as a wound dressing for dermal burn healing. Second-degree burn wounds were performed in forty-five Wistar rats, assigned into nine groups: COL—animals treated with collagen-based films; PHO—animals treated with collagen films containing empty liposomes; UAL—animals treated with collagen-based films containing usnic acid incorporated into liposomes. After 7, 14, and 21 days the animals were euthanized. On 7th day there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 37 publications
6
44
0
Order By: Relevance
“…The collagen matrix provides physical support for cellular proliferation, and its biodegradable and biocompatible properties make it suitable for wound dressing (16). In addition, incorporation of bioactive molecules, such as curcumin and usnic acid, into collagen-based films improves wound healing in experimental models (17,18).…”
mentioning
confidence: 99%
“…The collagen matrix provides physical support for cellular proliferation, and its biodegradable and biocompatible properties make it suitable for wound dressing (16). In addition, incorporation of bioactive molecules, such as curcumin and usnic acid, into collagen-based films improves wound healing in experimental models (17,18).…”
mentioning
confidence: 99%
“…The use of the usnic acid provided more rapid substitution of type-III for type-I collagen on the 14th day, and improved the collagenisation density on the 21st day. It was concluded that the use of reconstituted bovine type-I collagen-based films containing usnic acid improved burn healing process (Nunes et al, 2011). Differences in healing of wounds are summarized in histological sections in Figure 2.…”
Section: Films/membranesmentioning
confidence: 97%
“…MARINHO et al al. 2013), antitumoral (Santos et al 2006, Burlando et al 2009), antiviral (Sokolov et al 2012, Shtro et al 2014, anti-inflammatory (Vijayakumar et al 2000, Su et al 2014, antioxidant (Behera et al 2012, Suwalsky et al 2015, wound healing properties (Nunes et al 2011, Bruno et al 2013, antifungal (Halama and Van 2004, Nithyanand et al 2015, insecticide and larvicide (Sahib et al 2008, Bomfim et al 2009). …”
Section: Introductionmentioning
confidence: 99%